The sweetness of suffering community, conflict, and the cult of Saint Radegund in medieval Poitiers - Edwards, Jennifer C. (2008)
Abbesses in Medieval Europe demanded not just the obedience of their own nuns, but of any dependent communities, male or female. The authority of these women rested on the history of their communities, the strength of their advocates, and their own ability to pursue their rights. In Poitiers, the abbesses of Sainte-Croix built the strength of their office on the memory of their founder, Saint Radegund, who was a model for female authority and a symbol of the community. The abbesses drew on the charisma of the saint and on the network of supporters Radegund had established to protect the abbey. When abbatial authority was contested, these ecclesiastical and secular officials became reliable defenders of the abbess's position. The most enduring threats to the abbess of Sainte-Croix came from her own nuns and the chapter of Sainte-Radegonde, also founded by Radegund. Nuns from Sainte-Croix repeatedly questioned the merit of their abbesses, including two occasions that led to outbreaks of physical violence. The canons of Sainte-Radegonde also challenged the abbess's claims and flouted her authority. While the abbess insisted that Sainte-Radegonde was a dependent community obliged to serve Sainte-Croix, the canons sought to increase the independence of their chapter. The abbess interpreted the canons' efforts as unacceptable threats against her traditional privileges
Includes bibliographical references (leaves 210-238)
Keywords: History, Church; Women's Studies; History, Medieval; Hochschulschrift